Strategi Kesantunan Berbahasa Dalam Video Ceramah Ustadzah Oki Setiana Dewi Pada Media Youtube - Gebi Dwi Syafitri; Ermawati Arief (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The purpose of this study is to describe the types of politeness strategies used, the dominant language politeness strategies and determine the accuracy of using politeness strategies in Ustadzah Oki Setiana Dewi's video lectures on YouTube media. This type of research is a qualitative research with descriptive method. The data used in this study are speech fragments containing politeness in the video lectures of Ustadzah Oki Setiana Dewi. The data sources in this study were three video lectures with the most viewer views. The research instrument in this study was the researcher himself. Data collection techniques in this study were tapping and note-taking techniques. Validation of the data in this study is a triangulation technique (cross-check). The data analysis technique was carried out in the following stages. First, grouping speech fragments according to data sources. Second, provide data code. Third, classifying data. Fourth, describing and concluding the results of the research analysis. Based on the research conducted, it can be concluded that several politeness strategies were found in Oki Setiana Dewi's video lectures on YouTube media which include positive politeness strategies without preamble, negative politeness strategies without preamble, and vague speech strategies. The strategy of speaking frankly without further ado and the strategy of speaking silently cannot be found in Oki Setiana Dewi's video lectures. The dominant speech strategy used in Oki Setiana Dewi's video lecture is a strategy of speaking without preamble, positive politeness as much as 30 data.